IMPLEMENTASI SCRUM PADA FRAMEWORK SISTEM INFORMASI PENJUALAN DAN PEMBELIAN CAT PADA TOKO CAD - Emi Sita Eriana; Ghema Nusa Persada; Santosa Wijayanto (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT In the business world in the company's time that applies information technology because technology is needed in the world of work to facilitate in completing a job so that it is more effective and efficient. One example of the development of information technology in the world of work or the business world is data processing systems. In case studies in cad business units still use manual recording, the management and input process is still manual so it is less effective, efficient, and there are errors in recording inaccurately. Peneliti designed a web-based paint sales and purchase application where this application can facilitate the sale and purchase of paint without location limitations. This method in design uses the Agile method with its continuous development in a process called Scrum that overcomes complexity in the work by making it easier to understand and transparent, allowing teams to examine and adapt depending on current conditions, not the predicted scenario. The implementation of the scrum method is built with framework and MySQL databases. Hasil from research system sales and purchase of web-based paints facilitates purchases, so that customers can make purchases through the website indefinitely, where customers can buy and transact and make it easier for admins to make sales, with this paint sales and purchase system to support a wider market reach without location limitations. Keywords: Implementation, Scrum method, Framework, Design, Sales System